The Impact of Visual and Physical Programming-Based Science Activities on Middle School Students’ 21st Century and Computational Thinking Skills - Güneş, Habibe Kazez; Kucuk, Sevda (My University, 2025)
In the age of artificial intelligence, one of the main goals of education today is to produce innovative and productive individuals with 21st century skills, who can think creatively, solve problems, think critically, and have strong collaboration and communication skills. This study examines the impact of STEM-based lesson plans that incorporate knowledge-based life problems (APoKS) and visual-physical programming activities on middle school students' 21st century and computational thinking (CT) skills. The study involved 15 middle school students enrolled in a summer course and three science teachers. A 30-hour intervention was delivered over two weeks, covering topics such as the solar system, force and motion, renewable energy, electrical circuits and sound. Data were collected using the Computational Thinking Skills Self-Efficacy Perception Scale and the 21st Century Skills Scale. After implementation, educators provided insight through semi-structured interviews and reflective diaries. Quantitative data were analysed using the Wilcoxon Signed Rank Test, while qualitative data were examined using content analysis. Results indicate that the activities significantly improved students' 21st century thinking and CT self-efficacy. High impact improvements were observed in algorithm design, problem solving, data processing, programming and confidence. Educators confirmed these findings, noting the development of students' 21st-century and CT skills. Recommendations for future implementation and research are provided based on the findings.
Keywords: STEM; self-efficacy; 21st century skills; secondary school students; computational thinking; Programming